2022
DOI: 10.1038/s42005-022-01079-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards a robust criterion of anomalous diffusion

Abstract: Anomalous-diffusion, the departure of the spreading dynamics of diffusing particles from the traditional law of Brownian-motion, is a signature feature of a large number of complex soft-matter and biological systems. Anomalous-diffusion emerges due to a variety of physical mechanisms, e.g., trapping interactions or the viscoelasticity of the environment. However, sometimes systems dynamics are erroneously claimed to be anomalous, despite the fact that the true motion is Brownian—or vice versa. This ambiguity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 79 publications
(100 reference statements)
2
33
0
Order By: Relevance
“…The task of identifying a specific stochastic process and the best estimates of its parameters is hampered by the fact that measured data are compromised by the presence of detection noise. For unconfined motion the effects of both static and dynamic noise (as defined above) have been well studied, both from a conceptual point of view [72][73][74][75][76][77]81] and with respect to objective data analyses [58][59][60][61][62][63][64][65][66][67][68][69][70]. Here we presented a first approach to understanding the effects of static and dynamic noise on different normal-and anomalous-diffusion processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The task of identifying a specific stochastic process and the best estimates of its parameters is hampered by the fact that measured data are compromised by the presence of detection noise. For unconfined motion the effects of both static and dynamic noise (as defined above) have been well studied, both from a conceptual point of view [72][73][74][75][76][77]81] and with respect to objective data analyses [58][59][60][61][62][63][64][65][66][67][68][69][70]. Here we presented a first approach to understanding the effects of static and dynamic noise on different normal-and anomalous-diffusion processes.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of static and dynamic noise have been studied and methods how to remedy these effects proposed [77][78][79][80]. In particular, it was shown that power spectral analyses of single trajectories can still provide meaningful information on whether a measured dynamics is anomalous-or normal-diffusive [81]. Moreover, it was demonstrated that machine learning methods can provide reliable results for the trajectory analysis even in the presence of noise [69,70].…”
Section: Introductionmentioning
confidence: 99%
“…154,210,213,214 Recently it was demonstrated that the coefficient of variation of the PSD is a robust measure for anomalous diffusion in the presence of static and dynamic errors. 215…”
Section: E Power Spectral Densitymentioning
confidence: 99%
“…Importantly, for fixed ω > 0 and T → ∞, the coefficient of variation approaches a constant ω-independent value, dependent only on the spread of the process. It was thus suggested [31] (see also [32]) that γ can also serve as a robust criterion of anomalous diffusion-the issue to which we will return at the end of this paper. Moreover, the PDF reached in the T → ∞ limit depends on S(ω) = lim T →∞ S(ω, T ) and on its average μ(ω) only in the combination b ω = S(ω) μ(ω) .…”
Section: Introductionmentioning
confidence: 98%
“…These questions have been addressed in particular for the time series associated with blinking events in quantum dots [3], in standard Brownian motion [30] and in several anomalous diffusion processes [31][32][33][34], and also for the trajectories of the BG [35]. For instance, in [3] (see also [1] for some other examples) the distribution of S(ω, T ) was obtained for the time series of blinking events in quantum dots, and shown to converge to the exponential function in the limit T → ∞.…”
Section: Introductionmentioning
confidence: 99%